2014
DOI: 10.1177/2158244014538260
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Influence of Critical Psychological States on Work Engagement and Personal Outcomes in the Telecom Sector

Abstract: Organizations want their employees to be engaged with their work, exhibiting proactive behavior, initiative, and responsibility for personal development. Existing literature has a dearth of studies that evaluate all the three key variables that lead to optimal employee performance-critical psychological states (CPSs), work engagement, and personal outcomes. The present study attempts to fill that gap by linking the variable CPSs (which measures experienced meaningfulness, responsibility, and knowledge of resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other resources make things possible, but only engaged employees make things happen. Organizations do want their employees to be engaged with their work (Patrick & Bhat, 2014) as well as with their organization, which is one reason why employee engagement has become a buzzword in the business world. Kahn, well known as the first researcher who produced an academic paper on employee engagement in the year 1990 (Guest, 2014;Iddagoda et al, 2016), describes employee engagement as one's psychological presence when executing one's organizational tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Other resources make things possible, but only engaged employees make things happen. Organizations do want their employees to be engaged with their work (Patrick & Bhat, 2014) as well as with their organization, which is one reason why employee engagement has become a buzzword in the business world. Kahn, well known as the first researcher who produced an academic paper on employee engagement in the year 1990 (Guest, 2014;Iddagoda et al, 2016), describes employee engagement as one's psychological presence when executing one's organizational tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthopoulou et al (2007) found a positive relationship between employee engagement and self-efficacy, optimism, hope, resilience and organisational self-esteem. Research works by Patrick and Bhat (2014), on the relationship between employee engagement, critical psychological states and personal resources, found that employee engagement positively correlates with personal resources (optimism, hope and efficacy), indicating that work engagement enhances personal resources and that this can be attributed to the type of work employees do.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective leaders recognize an individual's value straight away; they trust them without asking them to earn it. Organizations want their employees to engage at work and exhibit proactive behavior, initiative, and responsibility for personal and organizational development (Patrick & Bhat, 2014). In this respect, valuing people may have a powerful, reciprocal effect on the organization's business culture (McNeff & Irving, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%